"LEVY’S FRUIT OF THE LEMON" (1999) AND THE CONSTRUCTION OF IDENTITY - Bonnici, Thomas (Línguas & Letras, 2000)
<!– @page margin: 2cm P margin-bottom: 0.21cm –> The slave-system, with extant repercussions on contemporary society, is accountable for the globalized exclusion scheme not only in the ex-colonies but even in the former metropolises. Official History is subverted by re-narrating what happened to non-Europeans during the last five hundred years and in Fruit of the Lemon black British author Andrea Levy utilizes orature to trigger the subjectification process in Faith Jackson, a British-born black female whose parents hail from Jamaica. Orature involve the construction of a new subject through revelations on the daily struggle for work, friendship, community-building, racial inclusion and the dire facts of the Caribbean diaspora. Since transindividual social tensions affect the British black subject, native or immigrant, the novel denounces the immigrants’ “amnesia” as a policy and the myth of a British multicultural society accepting peacefully ex-colonial subjects. Results show that remembrance through orature is a powerful means of subjectification and identity, besides being an antidote against a racialized society. In Fruit of the Lemon Levy installs an agonistic stance in which the authority of hegemonic discourse is subverted and a new liberating and hybridized discourse produced.